2021
DOI: 10.1007/s42770-021-00585-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of ERG gene expression in fluconazole-resistant human and animal isolates of Trichophyton verrucosum

Abstract: Dermatophytes are a group of eukaryotic microorganisms characterized by high capacity to colonize keratinized structures such as the skin, hair, and nails. Over the past years, the incidence of infections caused by zoophilic species, e.g., Trichophyton verrucosum, has been increasing in some parts of the world, especially in Europe. Moreover, the emergence of recalcitrant dermatophytoses and in vitro resistant dermatophytes has become a cause of concern worldwide. Here, we analyzed the mechanisms underlying re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(62 reference statements)
0
1
0
Order By: Relevance
“…The study of the relationship between the frequency of pathogenic genes and resistance to antifungal drugs showed that strains with polymorphic ERG genes were resistant to drugs, while strains without this gene family were sensitive to all antifungals (p<0.01). This association can be attributed to the mechanism of the polymorphic ERG gene in counteracting antifungal drugs ( 28 ). Ergosterol is a major component of yeast cell membrane sterols and is also responsible for maintaining cell function and integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The study of the relationship between the frequency of pathogenic genes and resistance to antifungal drugs showed that strains with polymorphic ERG genes were resistant to drugs, while strains without this gene family were sensitive to all antifungals (p<0.01). This association can be attributed to the mechanism of the polymorphic ERG gene in counteracting antifungal drugs ( 28 ). Ergosterol is a major component of yeast cell membrane sterols and is also responsible for maintaining cell function and integrity.…”
Section: Discussionmentioning
confidence: 99%